Mathematical Literacy Pattern Considered by Students’ Interests in ICARE Learning Through Smart Apps Creator with Performance Assessment (Universitas Negeri Semarang, 2022)
This study aims to find patterns of mathematical literacy in terms of student interest in ICARE learning through smart apps creators with performance assessments. This type of research is a mixed-method explanatory type, with a quasi-experimental type of nonequivalent control group design. The research subjects were students of class IXF SMP 1 Jekulo. Methods of collecting data are obtained by observation, literacy tests, and interviews. Data analysis was based on 7 components of mathematical literacy, namely communication, mathematization, representation, reasoning, and argumentation, planning strategies, using symbolic, formal, and technical language as well as arithmetic operations, and using mathematical tools. The results of the study there were 3 different literacy patterns for high, medium, and low interest. The pattern of students' interest in learning is high, the average mastery of the minimum components is good: very good all components and good representation; four components are excellent and good for mathematization, representation and using tools; four components are very good and good for mathematizing, planning strategies, and representation. The average pattern of mastery of the components is minimal enough: good for all components except for sufficient mathematization; the second and third patterns are almost the same, namely all are good except that they use sufficient tools. Meanwhile, for the low-average pattern, there are less-criteria: all components are good except for using symbols and category tools enough; all components are minimal enough except for lack of mathematization; everything is minimal enough and less to use symbols.